The role of middle managers in the NHS: the possibilities for enhanced influence in strategic change - Currie, Graeme (1999)
This thesis concerns the role of middle managers in strategic change in the NHS. It addresses a research gap identified by Dopson and Stewart (1990) who called for more empirical studies of the role of middle managers in specific contexts and highlighted the public sector as being of particular interest. It reports qualitative research carried out across 5 successive case studies in the NHS.